Power consumption of dosmetic refrigerator using nanoparticles Al2O3 lubricant mixture - Tey, Fanny Pei Boon (2013)
This paper studied the performance of a domestic refrigerator operating with or without nanoparticles alumina (Al2O3) lubricant mixture with different level of refrigerant charged into the refrigeration system. The nanoparticles Al2O3 lubricant mixture by volume concentration of 0.2% was prepared via two step method. The quantity of refrigerant charged by pressure was ranged from 36 psi to 44 psi. The evaluation was carry out by comparing the overall performance in term of refrigeration capacity (QL), compressor work (Win), coefficient of performance (COP) and power consumption for both sets of experimental testing. The refrigeration system of HFC134a/Al2O3/POE oil works normally and safely. From the results, the refrigeration performance for experiment operating with HFC134a/Al2O3/POE oil system was improved compared to HFC134a/ /POE oil system. Both refrigeration systems attained its optimum level at 42 psi charging pressure. The power consumption for HFC134a/Al2O3/POE oil system at optimum refrigerant charged which is 42 psi was the least with value 0.32 kW/h and the highest COP of 2.67. The percentage of increment in term of COP was between 2.81%, 3.59%, 3.89%, 4.55% and 5.91%. For the power consumption, the percentage of reduction was 1.47%, 1.61%, 1.80%, 2.07% and 1.77%. Thus, the addition of Al2O3 nanoparticles into the base fluid (POE) for better performance and reduction of power consumption was achievable.